Impact of bedrest on cardiovascular events and complications associated with temporary pacemakers in patients waiting for permanent pacemaker implantation. Issue 3 (30th March 2021) - Hama, Tomoaki; Morita, Norishige; Ushijima, Akiko; Ueno, Akira; Iida, Takayuki; Ikari, Yuji; Kobayashi, Yoshinori
Abstract: Background: Patients with a temporary pacemaker (TPM) for bradycardias are required to maintain bedrest until permanent pacemakers (PPMs) are implanted because of the development of Adams–Stokes syndrome, worsening heart failure, or complications associated with TPMs is anticipated. However, bedrest may be detrimental in patients because it leads to disuse syndrome. This study examined whether bedrest could decrease the incidence of cardiovascular events or complications associated with TPMs in patients waiting for PPM implantation. Methods: We conducted a retrospective cohort study on 88 patients who had emergency hospitalization for the treatment of bradycardias, and a TPM was inserted during the waiting period before PPM implantation. We divided patients into two groups according to whether they underwent bedrest (Bedrest Group) or not (Ambulation Group) during the period that patients were supported with TPM. We evaluated whether bedrest was a predictor of adverse events using a logistic regression analysis. Results: Adverse events occurred in 31 patients (35%). In the univariate analysis, there was no significant difference in the incidence of adverse events between the Bedrest and Ambulation Groups (39% vs. 29%). In the logistic regression analysis, bedrest was not a predictor of adverse events (odds ratio, 1.40; 95% confidence interval, 0.53‐3.68, P =  .497). Conclusions: In patients with TPMs for bradyarrhythmias during the waiting period for PPM implantations, bedrest might not prevent adverse events, such as cardiovascular events and complications associated with TPMs. Abstract : Bedrest might not prevent cardiovascular events or device complications in patients with a temporary pacemaker for bradyarrhythmias during the waiting period for permanent pacemaker implantation.